Indonesia's Strategy in Maritime Infrastructure Development Through China’s BRI - Ridho, Muhamad Syahadad (Department of Political Science - Universitas Sains Al-Qur’an, 2024)
This paper discusses Indonesia's strategy and initiative in maritime infrastructure development through cooperation under the Belt and Road Initiative (BRI) initiated by China. Maritime infrastructure development is a key component of Indonesia's vision as a Global Maritime Fulcrum, aimed at enhancing regional and global connectivity. Cooperation with BRI includes the construction and modernization of shipping routes, ports, and logistics facilities designed to accelerate goods flow, reduce logistics costs, and improve trade efficiency. Additionally, this strategic partnership is expected to attract foreign investment, stimulate economic growth, and create jobs. By utilizing China’s technology, funding, and expertise, Indonesia seeks to strengthen its position in the global supply chain and achieve inclusive and sustainable national development. This research highlights the importance of international collaboration in realizing resilient infrastructure development and its impact on economic growth and societal welfare.